Perancangan Interior Sekolah Musik Surabaya Symphony Orchestra di Surabaya - Liliyana Tan; I Gusti Ngurah Ardana; Grace Mulyono (Intra, 2016)
Classical music has a lot of benefits that can make more optimal brain development. Surabaya Symphony Orchestra Music School is a place to facilitate society in Surabaya to learn classical music.Many activities that can support learning classical music has not been facilitated due to the limited area, and lack of interior on SSO create interest and learning music became blocked. In accordance with Dolce concept which means “to play sweetly”, the music school design is using bright colors with soft and dynamic formation. Facilities available are practice studio, theory classroom, recording room, orchestra practice room, teacher’s office, staff office, administration office, recital hall, cafeteria, music store and book store.